Elemental Distribution in Animal Carpal and Tarsal Bones Using Differences in X-ray Fluorescence Energy - Tanita Pitakarnnop (2020)
© 2020, Springer Science+Business Media, LLC, part of Springer Nature. Little is known as to whether different operating voltages of X-ray fluorescence (XRF) can affect the accuracy rate for species identification. Here, we have addressed this question by comparing the rate of correct species identification using the elemental composition of either the carpal or tarsal bone obtained from a determination of the different energy values of XRF at 15 and 50 kV using energy-dispersive XRF (ED-XRF). Carpal bones were taken from 16 species and tarsal bones from 11 of these species. The data on the elemental profiles were analyzed by stepwise discriminant analysis for species discrimination. The classification results indicated that 94.1% and 63.7% of the originally grouped cases were correctly classified as carpal bones using 15 kV and 50 kV, respectively. Additionally, 69.4% and 77.3% of the originally grouped cases were correctly classified as tarsal bones using 15 kV and 50 kV, respectively. When the datasets of the elemental profiles obtained using two operating voltages were gathered, the classification results of the prediction rate appeared to be more accurate at 89.7% and 90.7% in the carpal and tarsal bones, respectively. In conclusion, our findings suggest that the elemental profiles of bones obtained using two operating voltages could effectively facilitate accurate species discrimination.